(untitled) (Foro de Educacion, 2026)
As education increasingly focuses on 21st-century skills, musical creativity has become a key priority, but there is still no unified theoretical framework. This study addresses this issue by systematically reviewing how musical creativity is defined, its measurable effects, and the factors that influence it in music education. Using PRISMA 2020 guidelines, we reviewed literature from Scopus, Web of Science, and EBSCOhost. After careful screening, 28 peer-reviewed articles from 2019 to 2025 were chosen for thematic analysis. The results show that musical creativity is complex and shaped by both how people think and how they interact with others, rather than being a single trait. The study found that creativity helps students become more independent and engaged in class, and it also encourages teachers to try new teaching methods. However, there is still a major gap in understanding how personal traits, such as frustration tolerance, interact with broader factors, such as curriculum policies, over time. The study suggests that while short-term programs work, lasting progress needs a focus on ongoing processes and learning environments that include technology and welcome everyone. These findings provide a stronger theoretical base and a clear direction for future long-term and international research in music education.